Synthesis Of Silver Nanoparticles Under The Influence Of Various Reducers - Lutpillayeva, Masuda; Hoshimov, Farhod (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
In this study, the synthesis of silver nanoparticles (AgNZ) with the participation of various reducing agents was studied. Silver nanoparticles have antibacterial, optical and biocompatible properties. The nature, concentration of reducing agents and the role of stabilizers in their synthesis are of great importance. In the study, silver nanoparticles were synthesized using AgNO₃ based on sodium citrate, hydrazine and glucose, and gelatin was used as a stabilizer. The resulting nanoparticles were confirmed by UV–Visible spectrum (peak 421 nm) and XRD analysis. Sodium citrate was identified as the most effective reducing agent. This method is an environmentally friendly, effective and economically viable solution.